Biomarkers in Inflammatory Bowel Disease-Associated Spondyloarthritis: State of the Art and Unmet Needs. (30th May 2019) - Benfaremo, Devis; Luchetti, Michele Maria; Gabrielli, Armando
Abstract : Inflammatory bowel disease-associated spondyloarthritis is a systemic disease characterized by the chronic inflammation of both the gastrointestinal tract and the musculoskeletal system. Since inflammatory bowel disease-associated spondyloarthritis has been associated with a significant diagnostic delay, which may lead to poor quality of life and progression of joint damage, efforts to discover new reliable and noninvasive diagnostic biomarkers have been made. We reviewed the state of the art of biomarker research in inflammatory bowel disease-associated spondyloarthritis, showing that to date it has been largely unsatisfactory. Only a few of the biomarkers that have been investigated are likely to enter the clinical practice upon further validation in independent cohorts. The research of new and innovative biomarkers for inflammatory bowel disease-associated spondyloarthritis is warranted.